(untitled) - Taylor, John G. (London, 1979)
The aim of this book is to remedy this situation by directing its critique at the basic concepts operative in these theories, assessing the extent to which thay can adequately analyse the structure, reproduction and development of third-world societies.
Keywords: Economic development,Historical materialism,Phát triển kinh tế,Lịch sử vật chất; Social aspects,Khía cạnh xã hội